Antimicrobial functionalization of bacterial nanocellulose by loading with polihexanide and povidone-iodine - Wiegand, Cornelia; Moritz, Sebastian; Hessler, Nadine; Kralisch, Dana; Wesarg, Falko; Mueller, Frank A.; Fischer, Dagmar; Hipler, Uta-Christina (Journal of Materials Science: Materials in Medicine, 2015)
Bacterial nanocellulose (BNC) is chemically identical with plant cellulose but free of byproducts like lignin, pectin, and hemicelluloses, featuring a unique reticulate network of fine fibers. BNC sheets are mostly obtained by static cultivation. Now, a Horizontal Lift Reactor may provide a cost efficient method for mass production. This is of particular interest as BNC features several properties of an ideal wound dressing although it exhibits no bactericidal activity. Therefore, BNC was functionalized with the antiseptics povidone-iodine (PI) and polihexanide (PHMB). Drug loading and release, mechanical characteristics, biocompatibility, and antimicrobial efficacy were investigated. Antiseptics release was based on diffusion and swelling according to Ritger–Peppas equation. PI-loaded BNC demonstrated a delayed release compared to PHMB due to a high molar drug mass and structural changes induced by PI insertion into BNC that also increased the compressive strength of BNC samples. Biological assays demonstrated high biocompatibility of PI-loaded BNC in human keratinocytes but a distinctly lower antimicrobial activity against Staphylococcus aureus compared to PHMB-loaded BNC. Overall, BNC loaded with PHMB demonstrated a better therapeutic window. Moreover, compressive and tensile strength were not changed by incorporation of PHMB into BNC, and solidity during loading and release could be confirmed.
CRIS-Team Scopus Importer:2020-10-13